PODCAST SEBAGAI MEDIA DIGITAL PADA MATERI INTERAKSI MANUSIA DENGAN LINGKUNGANNYA - Ulpah Samrotul Puadah; Nur Ela; Linda Aji Apriani; Dadan Nugraha (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the development process, the feasibility of podcasts as digital media on the material of human interaction with the environment. It is aimed to find out how social science learning subject material regarding human interaction with the environment that is packaged through digital podcast media, which is feasible to use and makes it easier to use and increases the listeners' understanding. The research was conducted online with the research subject of PGSD UPI students at Sumedang Campus. The research method used was the ADDIE research and development concept. The research concept of this ADDIE development model consisted of several stages, Analysis, Design, Develop, Implementation, and Evaluation. The instrument used was a questionnaire for media validation. Based on the results of the validation analysis, it could be concluded that the quality of the digital podcast media product developed was categorized into the appropriate category. It could be seen from the results of the evaluations that was carried out by several students, the first student, the second student with an average media validity score of 3.83 was categorized into a valid category. Language validity was 3.25 with a valid category and material validity was 4 with a very valid category, which was a previous total category average of 3.69. With the existence of the research, it is required that it could be a solution for the constraints of learning activities, especially the solutions regarding media in learning.